2010
DOI: 10.1211/jpp.62.06.0010
|View full text |Cite
|
Sign up to set email alerts
|

The application of feature selection to the development of Gaussian process models for percutaneous absorption

Abstract: The use of a nonlinear GPR method produced models with significantly improved predictivity, compared with SLN or QSPR models. Feature selection methods were able to provide important mechanistic information. However, it was also shown that significant synergy existed between certain parameters, and as such it was possible to interchange certain descriptors (i.e. molecular weight and melting point) without incurring a loss of model quality. Such synergy suggested that a model constructed from discrete terms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 52 publications
4
52
0
Order By: Relevance
“…However, Roberts and others [82–87] have shown that other parameters, particularly hydrogen bonding, are of importance. This has also been shown recently [16,20,88] . Indeed, Lam et al [16] .…”
Section: Methodssupporting
confidence: 67%
See 3 more Smart Citations
“…However, Roberts and others [82–87] have shown that other parameters, particularly hydrogen bonding, are of importance. This has also been shown recently [16,20,88] . Indeed, Lam et al [16] .…”
Section: Methodssupporting
confidence: 67%
“…Nevertheless, a major limitation to in‐vitro diffusion studies through excised human skin is the availability of suitable tissue. This has resulted in the widespread use of synthetic membranes and various animal models in place of excised human skin, and may impact upon the ability to develop representative models based on in‐vitro experimental data [16] . Studies comparing drug penetration across the skin of various animals with drug penetration across human skin have indicated that the skin of several animals provide excellent models for human skin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…See for example the seminal book [3] and the references therein for details. In chemometrics and related areas, GPR has been applied to a range of problems, such as calibration of spectroscopic analysers [4,5], response surface modelling [6], system identification [7], ensemble learning [5,8], prediction of transmembrane pressure [9], and prediction of percutaneous absorption [10,11], among others.…”
Section: Introductionmentioning
confidence: 99%